In the Wake of the Ongoing Mass Mortality Events: Co-occurrence of Mycobacterium, Haplosporidium and Other Pathogens in Pinna nobilis Collected in Italy and Spain (Mediterranean Sea) - Carella, Francesca; Antuofermo, Elisabetta; Farina, Simone; Salati, Fulvio; Mandas, Daniela; Prado, Patricia; Panarese, Rossella; Marino, Fabio; Fiocchi, Eleonora; Pretto, Tobia; De Vico, Gionata (Frontiers in Marine Science, 2020)
Following the Mass Mortality Events (MMEs) of the pen shell P. nobilis in Campania region and Sicily, a survey of moribund P. nobilis specimens was also conducted in other Italian regions (Campania, Tuscany, Sardinia and Apulia) and Spain (Catalunya). Histopathological and molecular examination of 27 specimens of P. nobils revealed different types of pathogens associated with tissue lesions, morbidity and mortality. Presence of Mycobacterium, Vibrio species, Haplosporidium pinnae and Perkinsus sp. were detected, differently distributed into the areas. The Mycobacterium sp., previously reported in Campania and Sicily samples, was observed in all the analysed areas and individuals, associated to systemic inflammatory lesions. In Spain, H. pinnae was observed in 36% of cases, always associated to the Mycobacterium sp.. Molecular study using hsp65 genes and Internal Transcriber Spacer ITS support that a new species of Mycobacteria is infecting P. nobilis, close to M. triplex and belonging to the group of M. simiae complex with M. sherrisi. Presence of Perkinsus spp. resembling P. mediterraneus was observed in 2 out of 13 Italian individuals whose presence should be addressed as potential risk for shellfish aquaculture of the area. Vibrio spp. were also detected in some case. The preliminary results of this study suggest that Mycobacterium sp., Vibrio spp., H. pinnae and Perkinsus sp. cooperate to disease pathogenesis, being Mycobacterium and Haplosporidium most of the time involved. Vigilant inspection of those areas where MME is now starting, along with continuous systematic surveys, are crucial to define the spatiotemporal progress of mortality and the role of every single pathogen in the disease outcome.